Numerical analysis of masonry-infilled RC-CLT panel connections - Mehdipour, Zabih (2022)
CLT panels have been investigated for reinforcement of existing masonry-infilled RC framed buildings through the increase of the overall lateral stiffness of the structure, thus reducing the story drift demand. The contribution of CLT panels depends on the connection to the RC frame elements. This paper evaluates the role of connectors by which CLT is attached to RC frames for capacity, ductility, and energy dissipation of the structure and its elements separately using different kinds of RC-CLT connections, and ultimately finds and compares the optimum number and arrangement of connectors. The results show that the geometry of connections plays a greater seismic role in RC frames than their mechanical properties. Regarding masonry infills, they allow a higher strength capacity but reduce the efficacy of CLT strengthening. However, strong connectors decrease the ability of infills in dissipation. Finally, in the optimum arrangement of connectors, they are distributed equally along the upper and lower beams at equal spacing, where CLT is added, starting in the middle of the beams and moving to the frame corners.